Analisis Penulisan Berita Pada Media Online Tvberita.co.id dan Pemanfaatannya Sebagai Bahan Ajar Modul Teks Berita di Kelas VIII - Resti Lisdaningsih; Roni Nugraha Syafroni; M. Januar Ibnu Adham (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study is entitled Analysis of News Writing on the online media Tvberita.co.id and Its Use as Teaching Materials for the News Text Module. The method used in this study is a qualitative descriptive method. Qualitative descriptive is collecting data by describing or describing data through descriptive words that describe the research subject. The aims of this research are to 1) describe news writing on the online media tvberita.co.id, 2) describe the systematics of writing news text elements, 3) describe the utilization of the analysis results of news writing on the online media tvberita.co.id as teaching materials for class VIII modules.